Peran Moderasi Islam dalam Mencegah Penyebaran Ideologi Ekstremisme di Indonesia - Nasution, Hasiolan; Lubis, Asep Ridwan (Moderasi : Journal of Islamic Studies, 2025)
Radicalism is a significant threat to social stability in Indonesia, especially among Muslim youth. This research aims to explore the role of Islamic moderation in preventing the spread of extremist ideology. This study uses a qualitative approach, the Systematic Literature Review (SLR) method with the framework of Preferred Reporting Items ¬for Systematic Reviews and Meta-Analyses (PRISMA), the study analyzed 100 studies from the Google Scholar database published between 2019-2024, with inclusion criteria covering the Muslim youth population aged 15-35 years. The results of the study show that Islamic moderation is effective in warding off radicalism through a multidimensional approach, including transformative education, digital media literacy, and strengthening the values of tolerance. The findings reveal that the implementation of Islamic moderation can build youth resilience against extremist propaganda, encourage comprehensive religious understanding, and create inclusive dialogue spaces. The conclusion of the study confirms that Islamic moderation is not just a theological approach, but a systematic strategy to form a tolerant and moderate young generation. This research makes theoretical and practical contributions to deradicalization efforts in Indonesia.